Strategi Pemasaran Digital Makanan Berat: Pembelajaran dari Praktek Kewirausahaan Mahasiswa STIKES Santa Elisabeth Medan 2024 - Pomarida Simbolon; Grace Putri Laia (Universitas Maritim AMNI Semarang, 2024)
The digital era has transformed marketing strategies in various industries, including culinary. This research examines the implementation of digital marketing strategies in selling heavy food by STIKES Santa Elisabeth Medan students as part of entrepreneurial practice. Involving 7 students who run an online culinary business for one day. Data is obtained through sales performance analysis. The results show that the use of social media and e-commerce websites increases market reach by 50% and sales by 35% compared to conventional methods. Personalized and interactive content strategies have proven to be the most effective, with engagement rates averaging 20% ​​higher. Key challenges include consistent management of digital platforms and adaptation to social media algorithms. Students also face difficulties in time management between studies and business. And also students who are carrying out activities also experience significant improvements in digital marketing and online business management skills. In conclusion, digital marketing provides great opportunities for students to develop entrepreneurial skills and improve culinary business performance. This research provides insight into effective digital marketing strategies for small-scale food businesses and can be a reference for entrepreneurship programs in universities